2021
DOI: 10.3389/fevo.2021.760368
|View full text |Cite
|
Sign up to set email alerts
|

Screening Candidate Effectors of the Bean Bug Riptortus pedestris by Proteomic and Transcriptomic Analyses

Abstract: The damage of Riptortus pedestris is exceptional by leading soybean plants to keep green in late autumn. Identification of the salivary proteins is essential to understand how the pest-plant interaction occurs. Here, we have tried to identify them by a combination of proteomic and transcriptomic analyses. The transcriptomes of salivary glands from R. pedestris males, females and nymphs showed about 28,000 unigenes, in which about 40% had open reading frames (ORFs). Therefore, the predicted proteins in the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Hemipterans, including R. pedestris , are major pests on crops, causing plant damage by piercing crop plants with their needle‐like mouthparts. During feeding, these insects inject secreted saliva into plant tissues to fix and digest nutrients, acting as effectors to facilitate feeding on the host plant (Fu et al, 2021 ; Huang et al, 2021 ). In recent years, with continuous technological advances, some salivary proteins acting as effectors were identified from white‐backed planthopper ( Sogatella furcifera ), brown planthopper ( Nilaparvata lugens ), green peach aphid ( Myzus persicae ), potato aphid ( Macrosiphum euphorbiae ), mirid bug ( Apolygus lucorum ), and white flies (Aleyrodidae) (Chaudhary et al, 2014 ; De Vos & Jander, 2009 ; Dong et al, 2020 ; Miao et al, 2018 ; Rao et al, 2019 ; Shangguan et al, 2018 ; Xu, Qian, et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hemipterans, including R. pedestris , are major pests on crops, causing plant damage by piercing crop plants with their needle‐like mouthparts. During feeding, these insects inject secreted saliva into plant tissues to fix and digest nutrients, acting as effectors to facilitate feeding on the host plant (Fu et al, 2021 ; Huang et al, 2021 ). In recent years, with continuous technological advances, some salivary proteins acting as effectors were identified from white‐backed planthopper ( Sogatella furcifera ), brown planthopper ( Nilaparvata lugens ), green peach aphid ( Myzus persicae ), potato aphid ( Macrosiphum euphorbiae ), mirid bug ( Apolygus lucorum ), and white flies (Aleyrodidae) (Chaudhary et al, 2014 ; De Vos & Jander, 2009 ; Dong et al, 2020 ; Miao et al, 2018 ; Rao et al, 2019 ; Shangguan et al, 2018 ; Xu, Qian, et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…R. pedestris is a polyphagous pest that is widely distributed in soybean-growing areas (Jung & Lee, 2019;.Our recent study has shown that R. pedestris feeding causes soybean staygreen syndrome, as shown by delayed leaf and stem senescence, abnormal pods, and aborted seeds (Wei et al, 2023). During feeding, R. pedestris inserts its sucking mouth into the tissues of the host plant to acquire water and nutrients, resulting in a reduction in soybean yield and seed quality (Bae et al, 2014;Fu et al, 2021). In recent years, soybean staygreen syndrome has expanded rapidly in soybean-growing areas in China (Zhang et al, 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…sativum) . The next generation of adults fly to flowering soybean fields, where their offspring cause damage by feeding on soybean pods. , Severely damaged plants are typically characterized by a lack of timely leaf senescence and an increase in seed abortion, the so-called “Staygreen Syndrome”, , similar to the “Stem Green Syndrome” in USA and Japan, , often leading to a complete abortion of the seed harvest . Therefore, the insect pest seems to synchronize the development of each generation with the phenology of local (wild) and agricultural Fabaceae plant species.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24] Assessing the distribution pattern of suitable habitats of potential and known pests can provide vital references for policymaking to manage and control them, and in this field, SDM has been widely applied to predict the potential distribution of pest species and to identify factors shaping their distribution pattern. [25][26][27] Although intense attention has been given to R. pedestris in recent years, most studies on this pest have focused on population dynamics and damage to soybean, 9,28,29 chemical ecology, 11,29,30 genomics and molecular biology, 8,31,32 and insecticide resistance and gut symbionts. 33,34 No investigation on the potential distribution of R. pedestris has been conducted to date, and the effects of ecological and anthropogenic factors on the distribution pattern of this important pest remain unknown, which greatly impedes the prevention and control of this pest.…”
Section: Introductionmentioning
confidence: 99%